1991
DOI: 10.1152/ajpgi.1991.261.3.g384
|View full text |Cite
|
Sign up to set email alerts
|

Jejunal mucosal injury and restitution: role of hydrolytic products of food digestion

Abstract: The effects of hydrolytic products of carbohydrate, protein, and lipid digestion on jejunal mucosal injury and restitution were assessed in anesthetized rats. Mucosal epithelial integrity was continuously monitored by measuring the blood-to-lumen clearance of 51Cr-labeled EDTA. Perfusion of the lumen with hydrolyzed casein (3%) or glucose (150 mM) did not affect 51Cr-EDTA clearance compared with saline controls. By contrast, perfusion with emulsified lipids (20 mM sodium taurocholate and 10-40 mM oleic acid) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
75
1

Year Published

1993
1993
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(81 citation statements)
references
References 0 publications
5
75
1
Order By: Relevance
“…In theory, dietary fat could increase LPS absorption in several ways. One way would be through promotion of paracellular uptake of macromolecules as a result of deleterious effects of fatty acids on tight-junction integrity (19). Our data do not support such a mechanism, for two reasons.…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…In theory, dietary fat could increase LPS absorption in several ways. One way would be through promotion of paracellular uptake of macromolecules as a result of deleterious effects of fatty acids on tight-junction integrity (19). Our data do not support such a mechanism, for two reasons.…”
Section: Discussioncontrasting
confidence: 78%
“…One possibility is that dietary fat promotes paracellular leakage of LPS across the intestinal epithelium. This is supported by the recent observations that intestinal-epithelial tight-junction integrity is compromised in obese mice (18) and by studies demonstrating that experimental intestinal luminal exposure to oleic acid (OA) can cause small-intestinal epithelial damage (19,20). An alternative possibility could be that LPS enters the body proper by transcellular transport through intestinal epithelial cells.…”
mentioning
confidence: 87%
“…These changes may involve subtle alttl.ations in permeability or, at higher detergent concentrations, more drastic effects such as membrane lysis and fusion (1 1). A concentration-dependent injury has also been observed in intestinal mucosa of developing piglets (7) and adult rats (8) after perfusion with bile acidsolubilized oleic acid. In fact, the concentration of fatty acids used in this study (5 mM) has been shown to produce a 20-fold increase in mucosal permeability in I-d-old piglet jejunum (7) and is associated with cell injury observed with light and electron microscopy (7).…”
Section: Discussionmentioning
confidence: 94%
“…Despite the important nutritional value of dietary fatty acids, these compounds have been implicated in the pathophysiology of intestinal mucosal injury in developing (6,7) and adult animals (8,9). We have shown that perfusion of developing piglet intestine with oleic acid, a long-chain dietary fatty acid, produces dose-dependent increases in mucosal permeability as quantitated by the plasma-to-lumen clearance of 5'Cr-labeled EDTA.…”
mentioning
confidence: 95%
“…An interesting finding was the ileal mucosal thinning observed in both P2Y 13 +/+ and P2Y 13 −/− mice fed with HFD. Previous studies have shown lipid infusions, unlike other nutrients, to cause a mucosa barrier impairment in the rat small intestine [26].…”
Section: Lipid-induced Neuronal Lossmentioning
confidence: 89%